Hubungan sikap, pengaruh sosial, jangkaan bersalah, niat dan tingkah laku pembelian produk tiruan dalam kalangan pengguna di Malaysia - Azli, Muhammad (2017)
Counterfeiting refers to illegally making copies of trademark, patent, and copyright of product without permission from the owner with the aim to reap the benefits offered by a branded product. Counterfeiting is a phenomenon that has long been neglected in previous studies. Production and sale of counterfeit products is an issue that has no ending, and becoming an increasingly serious problem in the international market in general and Malaysian market in particular. Based on Theory of Planned Behaviour, this study focuses on the factors that influence the purchase intention and behavior among consumers towards counterfeit products in Malaysia. This study examined the relationships between attitudes, social influence, perceived behaviour control, anticipated guilt and past experience on intention and purchase behavior of counterfeit products. The consideration of putting both mediator and moderator factors in this research allow a more previse descriptions on the relationship between all the variables mentioned and the outcome of the research. This study involved 392 respondents in the area of Kuala Lumpur, Penang and Johor Baharu who have experience buying counterfeit products. Out of seven hypotheses tested, six were supported. The analyses revealed positive relationship between intention and purchase behaviour of counterfeit products. Attitudes and social influence have positive relationships with intention to purchase counterfeit products while perceived behavioural control has positive influence on purchase behaviour of counterfeit products. Anticipated guilt mediates the relationship between attitude and intention to purchase counterfeit products while past experience moderates the relationship between intention and purchase behaviour of counterfeit products. The study also highlighted implications of the study, limitations as well as suggestion future research.